Technology, Organization, Environment, and Digital Transformation for Sustainability - Siti Annisa; Mohammad Riza Sutjipto (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The demands of digital transformation and intense competition are affecting Indonesia's insurance industry. PT Jasaraharja Putera needs to adopt digital technology to enhance productivity and competitiveness. This research utilizes digital transformation as a mediating variable to analyze the impact of organizational, environmental, and technological elements on sustainable advantage through the Technology-Organization-Environment (TOE) framework. The quantitative approach used is Structural Equation Modeling-Partial Least Squares (SEM-PLS) analysis. The Slovin formula analyzed data gathered from 227 participants. The results indicated that organizational (t=8.364; p=0.000) and technological (t=2.432; p=0.015) factors considerably influenced digital transformation. Environmental factors significantly influence outcomes (t=3.871; p=0.000). Digital transformation is crucial for enhancing sustainable excellence (t=3.773; p=0.000). Moreover, the indirect influence of the three TOE factors on sustainable advantage via digital transformation is also noteworthy (e.g., X2 → Z → Y, t=3.152; p=0.002). This study adds to the theoretical understanding by validating the significance of the TOE framework within the insurance sector and offers actionable insights for PT Jasaraharja Putera’s management to enhance organizational preparedness for technology adoption, foster HR capabilities, and bolster technology integration in customer service to maintain competitiveness. This study focuses on a single company, so applying the findings more broadly should be approached carefully. It is suggested that upcoming studies include a wider range of subjects from various sectors and locations.